Assessment of the Microbiological Profile, Species Diversity and Antimicrobial Susceptibility of Recovered Bacteria from Retail Honeys in Turkey - GURAN, HS; DURUKAN, G; MANN, D (Journal of the Hellenic Veterinary Medical Society, 2021)
The aim of this study was to assess the microbiological profile, coliform and staphylococcal species diversity, and the antimicrobial susceptibility of coliform and other Gram-negative bacteria recovered from retail honeys in Turkey. A total of 150 honey samples, including extracted honey and comb honey samples, were purchased from honey sellers. The honey samples were analyzed for total mesophilic aerobic bacteria (TMAB), total mesophilic anaerobic bacteria (TMAnB), coliforms, Escherichia coli (E. coli), Staphylococcus spp., lactic acid bacteria (LAB), yeasts, and molds. All presumptive coliform and Staphylococcus isolates were identified at species level and then Gram-negative isolates were screened for antimicrobial susceptibility. TMAB, TMAnB, LAB, yeasts and molds mean counts (log cfu/g) in the samples were 3.26±1.08, 3.0±0.89, 2.93±0.52, 2.90±0.83, 1.80±0.53, respectively. Eighteen point seven percent and 15.3% of extracted and comb honey contained coliform and Staphylococcus spp., respectively, with a mean count (MPN/g) of 8.06±1.23 and 0.71±0.66. TMAB, Staphylococcus spp. and yeast contamination rates were significantly higher in the extracted honeys (P<0.05). Presumptive coliform and Staphyloccus spp. isolates were mostly identified as Klebsiella pneumoniae, Proteus mirabilis, Serratia marcescens, and Staphylococcus hominis and Staphylococcus epidermidis, respectively. Among coliform and non-coliform Gram-negative recovered isolates, antimicrobial resistance was highest against ceftriaxone (92.4%) and cefepime (91.5%) followed by tigecyclin (46.2%). The results obtained in this study provide insight on the microbiological profile of honey and the diversity of coliform and Staphylococcus species in honey samples. Moreover, these results show that honey, which is considered beneficial for human health, may contain antibiotic-resistant bacteria.